Oligonucleotides Featuring a Covalently Mercurated 6-Phenylcarbazole Residue as High-Affinity Hybridization Probes for Thiopyrimidine-Containing Sequences - Kotammagari Tharun K; Tähtinen Petri; Lönnberg Tuomas (WILEY-V C H VERLAG GMBH, 2022)
Short oligonucleotides incorporating either 1-mercuri-6-phenylcarbazole, 8-mercuri-6-phenylcarbazole, or 1,8-dimercuri-6-phenylcarbazole C-nucleoside in the middle of the chain have been synthesized and studied for their potential as hybridization probes for sequences containing thiopyrimidine nucleobases. All of these oligonucleotides formed very stable duplexes with complementary sequences pairing the organometallic moiety with either 2- or 4-thiothymine. The isomeric monomercurated oligonucleotides were also able to discriminate between 2- and 4-thiothymine based on the different melting temperatures of the respective duplexes. DFT-optimized structures of the most stable mononuclear Hg-II-mediated base pairs featured a coordinated covalent bond between Hg-II and either S2 or S4 and a hydrogen bond between the carbazole nitrogen and N3. The dinuclear Hg-II-mediated base pairs, in turn, were geometrically very similar to the one previously reported to form between 1,8-dimercuri-6-phenylcarbazole and thymine and had one Hg-II ion coordinated to a thio and the other one to an oxo substituent.